Cartografia dos sentidos: modos do fazer, experiência estética e aprendizagem - Marlette Aparecida Rezende de Menezes (2015)
Cartography of the senses is the result of an investigation into the act of doing, the aesthetic experience and the practice of teaching and learning in the field of art; the aim was to articulate theory and practice in order to draw paths, maps of meanings, of what inputs movement to the aesthetic experience and the learning act. The starting point was given by the reports based on experience from workshops held with various social subjects in urban and rural communities in Brazil. Such reports provoked worries and thoughts concerning the relations and ways of doing of the participants within teaching and learning situations in the field of symbolic production of art among handcraft. It is a reflection involving the correlation of substances, ways of doing, matter and ambience in the conjunction of subjectivities and diverse interests which converge in the fields of cultural production of the craft. Along these lines of thought, practising and searching some questions emerged: how to urge moments of aesthetic experience in processes of teaching and learning in arts when the legacy of the tradition dialogues with contemporary ways of doing? How is the connection between experience and learning made? What is, or what are the principles that drive to the act of doing in an aesthetic manner? The result is then a theoretical and practical speculation following the capture and production of a map of the meanings involving learning and teaching experiences in art, in the processes of knowledge construction and symbolic meaning over different space-times.